2011
DOI: 10.1038/ejhg.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

The desmosterolosis phenotype: spasticity, microcephaly and micrognathia with agenesis of corpus callosum and loss of white matter

Abstract: Desmosterolosis is a rare autosomal recessive disorder of elevated levels of the cholesterol precursor desmosterol in plasma, tissue and cultured cells. With only two sporadic cases described to date with two very different phenotypes, the clinical entity arising from mutations in 24-dehydrocholesterol reductase (DHCR24) has yet to be defined. We now describe consanguineous Bedouin kindred with four surviving affected individuals, all presenting with severe failure to thrive, psychomotor retardation, microceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 19 publications
0
53
1
Order By: Relevance
“…Two cases including our patient had relative macrocephaly (Schaaf et al, 2011). Only one previous patient was reported to have macrocephaly (FitzPatrick et al, 1998) (> 97 percentile), 5 other cases had microcephaly (Andersson et al, 2002; Zolotushko et al, 2011) and two were normocephalic (Dias et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two cases including our patient had relative macrocephaly (Schaaf et al, 2011). Only one previous patient was reported to have macrocephaly (FitzPatrick et al, 1998) (> 97 percentile), 5 other cases had microcephaly (Andersson et al, 2002; Zolotushko et al, 2011) and two were normocephalic (Dias et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Andersson et al reported the first living case of desmosterolosis in an infant who presented with severe microcephaly, agenesis of corpus callosum, facial dysmorphic features, clubfoot and persistent patent ductus arteriosus, and a 100-fold increase in the level of desmosterol both in plasma and cultured lymphoblasts (Andersson et al, 2002). Zolotushko et al (2011) described a consanguineous Israeli Bedouin family with six affected family members of which four were living. All affected individuals described had microcephaly, microretrognathia, psychomotor and growth retardation, hand contractures, underdeveloped corpus callosum and ventriculomegaly (Zolotushko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmosterolosis is an inborn error of cholesterol synthesis due to mutations in the gene that encodes 24-dehydrocholesterol reductase ( DHCR24 ) [FitzPatrick et al, 1998; Andersson et al, 2002; Zolotushko et al, 2011; Schaaf et al, 2011]. No disease-specific treatment is available, and the focus is on symptomatic care, similar to that in SLOS.…”
Section: Future Studies In Slosmentioning
confidence: 99%
“…Genetic errors affecting transformations that are early in the biosynthesis pathway are generally lethal at preimplantation or the very early embryonic stage, while individuals with inborn errors affecting the last steps of cholesterol biosynthesis can survive to birth, usually with severe consequences. 516 …”
Section: Introductionmentioning
confidence: 99%